Ecological effects of extreme climatic events on riverine ecosystems: insights from Australia. (23rd December 2014) - Leigh, Catherine; Bush, Alex; Harrison, Evan T.; Ho, Susie S.; Luke, Laurisse; Rolls, Robert J.; Ledger, Mark E.
Summary: Climate extremes and their physical impacts – including droughts, fires, floods, heat waves, storm surges and tropical cyclones – are important structuring forces in riverine ecosystems. Climate change is expected to increase the future occurrence of extremes, with potentially devastating effects on rivers and streams. We synthesise knowledge of extremes and their impacts on riverine ecosystems in Australia, a country for which projected changes in event characteristics reflect global trends. Hydrologic extremes play a major structuring role in river ecology across Australia. Droughts alter water quality and reduce habitat availability, driving organisms to refugia. Extreme floods increase hydrological connectivity and trigger booms in productivity, but can also alter channel morphology and cause disturbances such as hypoxic blackwater events. Tropical cyclones and post‐cyclonic floods damage riparian vegetation, erode stream banks and alter water quality. Cyclone‐induced delivery of large woody debris provides important instream habitat, although the wider ecological consequences of tropical cyclones are uncertain. Wildfires destroy catchment vegetation and expose soils, increasing inputs of fine sediment and nutrients to streams, particularly when followed by heavy rains. Research on the impacts of heat waves and storm surges is scarce, but data on temperature and salinity tolerances, respectively, may provide some insight into ecological responses. We identify research gaps and hypotheses to guide future research on the ecology of extreme climate events in Australia and beyond. A range of phenomenological, experimental and modelling approaches is needed to develop a mechanistic understanding of the ecological impact of extreme events and inform prediction of responses to future change.